The method of detecting leaks in pneumatic actuators on the example of a selected production system - Loska, Andrzej; Macha, Artur (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2025)
Compressed air is a very important energy medium in industrial processes. Maintained at a pressure higher than atmospheric pressure, it is one of the most commonly used working mediums. Leaks in pneumatic systems, inappropriate pressure, improper use of components, etc. are responsible for losses of produced compressed air. Pneumatic actuators, which are key in this respect, are exposed to internal and external leaks, which leads to an increase in their extension and retraction time, a decrease in the force achieved on the piston rod, and in the case of large leaks - to their stopping, causing a failure and necessary downtime of the machine or the entire production line. The article addresses the problem of leaks in pneumatic actuators used within automated production systems. The specificity of operation of pneumatic actuators, problems with their leaks, and available methods of their detection are discussed. For the needs of the tested production system, an original method for detecting leaks in pneumatic actuators was developed, the operation of which was verified using a simulation model in the Simulink environment. The performed analysis allowed to confirm the correctness of the developed method.